Advanced large language models and visualization tools for data analytics learning - Valverde-Rebaza, Jorge; González, Aram; Navarro-Hinojosa, Octavio; Noguez, Julieta (Frontiers in Education, 2024)
Considering the ubiquitous impact of Artificial Intelligence (AI) in daily life, it is imperative to leverage AI tools to tackle challenges across various sectors, including education. In recent years, numerous AI tools have been employed to equip learners with diverse technical skills such as coding, data analysis, and other competencies related to computational sciences. However, the desired outcomes have not been consistently achieved. Given the recent surge and widespread adoption of applications based on Large Language Models (LLMs), also known as generative AI tools, there is growing interest in harnessing these technologies as allies in the process of acquiring technical skills. One of the most popular generative AI tools for this purpose is ChatGPT. The effectiveness of ChatGPT as a coding assistant and support tool for learning programming has mainly been assessed among students and professionals who already possess advanced computational thinking skills. Thus, there remains a significant gap in understanding the impact of generative AI technologies as tools to support the learning process of programming skills, and more critically, data analytics-related competencies. This study aims to analyze the perspectives of students and professionals from non-computational fields on the use of generative AI tools, augmented with visualization support, to tackle data analytics projects. The focus is on promoting the development of coding skills and fostering a deep understanding of the solutions generated. Consequently, our research seeks to introduce innovative approaches for incorporating visualization and generative AI tools into educational practices.